2021
DOI: 10.18203/2320-6012.ijrms20210879
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between iron metabolism and thyroid hormone profile in hypothyroidism

Abstract: Background: Iron and thyroid hormone metabolism are closely related with each other. Iron plays an important role for both the synthesis as well as metabolism of thyroid hormones acting as a component of many enzymes including thyroid peroxidase (TPO). So, iron deficiency can lead to abnormal functioning of thyroid gland. Ferritin is storage form of iron in our body. Several studies in showed that nutritional iron deficiency can significantly decrease the circulating levels of both T4 and T3 and it can also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…In this study, we found that there was statistically significant relationship between iron deficiency anemia and hypothyroidism. The findings of our study were similar to that of study conducted by Chatterjee et al 1 Similarly, in a randomized double blind controlled study done by Ravanbod M et al 12 demonstrated that treatment of patients with subclinical hypothyroidism and iron-deficiency anemia with a combination of iron levothyroxine resulted in a favorable outcome compared with treatment of patients with monotherapy of iron or levothyroxine alone. The study conducted by Binita et al showed, there was no statistically significant relations of thyroid dysfunction in patient with IDA in Lalitpur Nepal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we found that there was statistically significant relationship between iron deficiency anemia and hypothyroidism. The findings of our study were similar to that of study conducted by Chatterjee et al 1 Similarly, in a randomized double blind controlled study done by Ravanbod M et al 12 demonstrated that treatment of patients with subclinical hypothyroidism and iron-deficiency anemia with a combination of iron levothyroxine resulted in a favorable outcome compared with treatment of patients with monotherapy of iron or levothyroxine alone. The study conducted by Binita et al showed, there was no statistically significant relations of thyroid dysfunction in patient with IDA in Lalitpur Nepal.…”
Section: Discussionsupporting
confidence: 91%
“…So, deficiencies of these elements can impair thyroid functions. 1 Iron is one of the essential elements for the thyroid gland to function properly and it is stored in the form of ferritin. 2 First two initial steps of thyroid hormone biosynthesis require an iron containing enzyme known as thyroperoxidase (TPO), which is a membrane bound glycosylated protein.…”
Section: Relationship Between Serum Ferritin and Thyroid Hormones: A ...mentioning
confidence: 99%
“…8 Many studies suggest that iron deficiency impairs thyroid hormone metabolism in both animals and humans. 9,10,11 Iron deficiency has also been shown to decrease plasma T3 and T4 concentrations while increasing in vitro hepatic reverse T3 (rT3) deiodination, implying that iron deficiency affects thyroid hormone metabolism via a deactivating pathway. T4 is transformed to T3, however a large part is converted to rT3, a physiologically inactive metabolite.…”
Section: Introductionmentioning
confidence: 99%